Elhaló aprófaluból dinamikusan fejlődő fürdőváros - Halász, Imre (Közép-Európai Közlemények, 2016)
Before the appearance of a new natural resource in the life of the small southern Zala village, in the fifties and sixties the village did not differ from other settlements of a few hundred inhabitants. It had a life that was typical in Hungarian villages of the era, where the cooperative was the only economic organization that provided jobs.The change, however, has not started with the discovery of thermal water and the establishment of the spa. At the beginning, when tourism was identified as a branch of domestic trade, neither a significant economic development, nor a social change can be detected. As soon as the conscious, -a bit later –the integrated settlement development started, this tendency has changed rapidly. Building the thermal bath was a milestone, its development triggered a series of changes. First, migration from the village stopped, the population was stagnant for a while, then more and more people settled down in the village.The process of change can be observed in the administrative status of the settlement as well. Initially, it was an associate commune, later an independent district village council was in charge of governing anddevelopment duties, then it became a large commune / village (1984), later –at its inauguration –the smallest town of Hungary (1997).The changes of the past half, or rather quarter of the century have brought interesting features in the life of the local society where integration has appeared instead of fragmentation.